Association of GHR|AluI gene polymorphism with body weight parameters in Grati-PO cattle - Hartati, H.; Hapsari, A.A.R.; Soewandi, B. D. P.; Anwar, S.; Rahmadani, S. P.; Aryogi, A.; Pamungkas, D. (Journal of the Indonesian Tropical Animal Agriculture, 2021)
The growth hormone receptor (GHR) gene is member of the class I cytokine receptor family that important in growth regulation including in cattle. This study aimed to analyze the association between GHR|AluI gene with body weight, parameters in Grati-PO cattle population. A total of 304 blood samples were collected from the experimental station at the Beef Cattle Research Station, which were also equipped with 304 phenotypic data. DNA was extracted using a zymo extraction kit. Detection of of the polymorphism of GHR gene using PCR-RFLP method with AluI restriction enzymes. polymorphism indicators include genotype frequency, allele frequency, Hardy-Weinberg Equilibrium, observed heterozygosity (Ho), expected heterozygosity (He), polymorphism information content (PIC) and number of effective alleles (Ne). Association analysis was carried out using a linear mixed model. The performance of birth weight, weaning weight, yearling weight and 18 months weight were 25.4 + 0.2 kg; 113.8 + 2.3 kg; 159.9 + 2.7 kg and 213.7 + 3.6 kg, respectively. The result of association analysis was significant (P<0.05) on weaning weight, yearling weight and 18 months weight. It could be concluded that the GHR gene has potential to be a candidate genetic marker for growth traits in Grati-PO cattle.